Calvicie masculina antes de los 35 años de edad como factor de riesgo de cáncer de próstata - Loja Vega, Elmer (2014)
To determine whether rnale baldness before age 35 is a risk factor for prostate cancer. METHODS: Restrospective caso-control study in Hospital Regional Docente de Trujillo (HRDT) during the period October 2013 to January 15, 2014. An interview with the patients underwent and also the rnedical records reviewed of patients who forrned cases. The cases consisted of 40 patients with a diagnosis of prostate cancer and controls consisted of 120 patients without prostate cancer. The association of the study factors was determined by the Chi-square test (X²) and quantified by the Odds Ratio (OR), p <0.05. RESULTS: 33% of patients with prostate cancer presented the beginning of his baldness before age 35; however this was presented only 14% of patients without prostate cancer. Also found that baldness before age 35 was a risk factor for prostate cancer (X2: 6.62, OR: 2.91, CI: 1.26-6.74, P = 0.01); however no was found relationship between PSA values > 20 ng / rnl, Gleason Score values 7 sorne pattern baldness (p 0.87 and p=0.69 respectively). CONCLUSIONS : Baldness before age 35 is a risk factor for prostate cancer, however PSA values > 20ng/rnl and Gleason Score values >= 7 no are factors associated with sorne pattern baldness